Origin of Fossiliferous Limestone Beds inside the Upper Part of Tanjero Formation at the Northwest of Sulaimani Area, Kurdistan Region, NE-Iraq - Karim, K H.; Ismail, Kh M.; Baziany, M M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
The present study is focused on origin of fossiliferous limestone beds that are exposed in the Chaqchaq Valley at 10 kms to northwest of Sulaimani city. These beds are exposed inside upper part of the Tanjero Formation (Upper part of Gurpi Formation in Iran) and, in this study, they are call Chaqchaq limestone. The petrography and age determination proved that they aged Late Maastrichtian and belongs to Aqra Formation (Seymare or Tarbur Formation in Iran). These beds represent the extreme distal facies of the formation. The fossil contents of these beds include large foraminiferas (Omphalocyclus, Orbitoids and Loftusia), fragments of Rudists in addition to solitary corals, echinoderm and gastropods.These fossils are all allochthous and reworked by submarine mass wasting from their original life position in Chwatra–Mawat area. As the discovered outcrops are located, stratigraphically, near the boundary of Cretaceous and Tertiary ages, it has important contribution on changing paleo-geography and tectonism of northeastern Iraq during Maastrichtian and Paleocene. The paleogeography of the area was consisted of large foreland basin that was covered all north eastern Iraq without any compartmentation. Previously Aqra Formation is recorded in the Imbricated and Thrust Zones while the present study records it in the High Folded Zone for the first time in the Northeastern Iraq. This record will remove the uncertainty that associated with the relations of the stratigraphic units in the Imbricated and Thrust Zones with those of High Folded Zones. In these zones, Tanjero Formation (with Aqra Formation) and Red Bed Series are deposited during Maastrichtian and Paleocene. The occurrence of these beds inside hemiplelagite (upper part of Tanjero Formation), make the age determination of the beds and their equivalent (Aqra Formation) in the Chwarta Mawat area are possible by planktonic forms. The planktonic foraminiferas show that the age of these beds (Chachaq Limestone) is late Maastrichtian.
Keywords: Aqra Formation Late Maastrichtian Carbonate turbidite Chaqchaq Valley Limestone Sulaimani Governorate Kurdistan Region; Iraq